Fasted and fed small bowel motility patterns at cine‐MRI in chronic intestinal pseudo‐obstruction. Issue 6 (27th December 2020) - van Rijn, Kyra L.; Bredenoord, Albert J.; Smout, André J. P. M.; Bouma, Gerd; Tielbeek, Jeroen A. W.; Horsthuis, Karin; Stoker, Jaap; de Jonge, Catharina S.
Abstract: Background: Chronic intestinal pseudo‐obstruction (CIPO) is a severe intestinal motility disorder of which the pathophysiology is largely unknown. This study aimed at gaining insight in fasted and fed small bowel motility in CIPO patients using cine‐MRI with caloric stimulation. Methods: Eight adult patients with manometrically confirmed CIPO were prospectively included. Patients underwent a cine‐MRI protocol after an overnight fast, comprising fasting‐state scans and scans after ingestion of a meal (Nutridrink, 300 kcal). Small bowel motility was quantified resulting in a motility score in arbitrary units (AU) and visually assessed by three radiologists. Findings were compared with those in 16 healthy volunteers. Key Results: Motility scores (median, IQR) in CIPO patients were 0.21 (0.15–0.30) in the fasting state and 0.23 (0.15–0.27) directly postprandially. In healthy volunteers, corresponding motility scores were 0.15 (0.13–0.18) and 0.22 (0.19–0.25), respectively. The postprandial change in motility score was +1% (−19 to +21%) in CIPO and +39% (+23 to +50%) in healthy volunteers ( p  = 0.001*). Visual analysis revealed increased small bowel contractility in four, normal in two, and decreased in two CIPO patients. Conclusions & Inferences: Surprisingly, we found hyperactive small bowel motility in half of the CIPO patients, suggestive of uncoordinated motility. A wide variation in motility patterns was observed, both higher, lower, and comparable contractility compared with healthy subjects. No clear postprandial activation was seen in patients. Cine‐MRI helps to gain insight in this complex disease and can potentially impact treatment decisions in the future. Abstract : Fasted and postprandial small bowel motility measured with cine‐MRI is variable in CIPO patients, ranging from decreased to increased compared to healthy volunteers. Cine‐MRI helps to gain insight in this complex disease and can potentially impact treatment decisions in the future.